The role of global dynamic managerial capability in the pursuit of international strategy and superior performance - Tasheva, Sabina; Nielsen, Bo Bernhard (Journal of International Business Studies, 2022)
We develop the construct of global dynamic managerial capability (GDMC) and identify its underlying sources: (1) international human capital, (2) international social capital, and (3) international managerial cognitions. Consistent with dynamic capabilities view and upper echelons theory, we suggest that GDMC leads to global asset orchestration, which in turn, results in superior company performance in a two-stage process. First, GDMC leads companies to adopt global strategies that spread the risk of internationalizations across different entry modes and geographic regions. Second, the (re)configuration of global assets positively influences subsequent firm performance and thus mediates the relationship between GDMC and performance. Recognizing the triad of factors that form global dynamic managerial capability is crucial when selecting future managers of multinational corporations. Hence, firms with increasing international exposure – both domestically via foreign competition and internationally via foreign market presence – may seek to compose their upper echelons with a suitable combination of international human and social capital as well as internationally diverse cognitions in the pursuit of sustained competitive advantage.